Reorganization of Ventral Premotor Cortex After Ischemic Brain Injury: Effects of Forced Use. (August 2022) - Frost, Shawn B.; Chen, Daofen; Barbay, Scott; Friel, Kathleen M.; Plautz, Erik J.; Nudo, Randolph J.
Background: Physical use of the affected upper extremity can have a beneficial effect on motor recovery in people after stroke. Few studies have examined neurological mechanisms underlying the effects of forced use in non-human primates. In particular, the ventral premotor cortex (PMV) has been previously implicated in recovery after injury. Objective: To examine changes in motor maps in PMV after a period of forced use following ischemic infarct in primary motor cortex (M1). Methods: Intracortical microstimulation (ICMS) techniques were used to derive motor maps in PMV of four adult squirrel monkeys before and after an experimentally induced ischemic infarct in the M1 distal forelimb area (DFL) in the dominant hemisphere. Monkeys wore a sleeved jacket (generally 24 hrs/day) that forced limb use contralateral to the infarct in tasks requiring skilled digit use. No specific rehabilitative training was provided. Results: At 3 mos post-infarct, ICMS maps revealed a significant expansion of the DFL representation in PMV relative to pre-infarct baseline (mean = +77.3%; n = 3). Regression analysis revealed that the magnitude of PMV changes was largely driven by M1 lesion size, with a modest effect of forced use. One additional monkey examined after ∼18 months of forced use demonstrated a 201.7% increase, unprecedented in non-human primate studies. Conclusions: Functional reorganization in PMV following an ischemic infarct in the M1 DFL is primarily driven by M1 lesion size. Additional expansion occurs in PMV with extremely long periods of forced use but such extended constraint is not considered clinically feasible.